ETIOLOGY OF UROLITHIASIS FROM SOUTH INDIAN POPULATION: CORRELATION OF RECURRENCE AND ANTIBIOTIC RESISTANCE TO BIOFILM PRODUCTION CAPABILITIES OF UROPATHOGENIC MICROBES. - B.JANAKIRAM; T.SUNITHA; M.RAMESH BABU; GUNTUPALLI.SWAPNA; B.CHANDRA SEKHAR; BONDILI J S (International Journal of Pharma and Bio Sciences, 2014)
Kidney stone formation is one of the most painful and widespread urological disorders. In this study, the prevalence of renal calculi in relation to urinary tract infections was investigated in 125 patients from Southern India. The chemical composition and bacteriological study of pre, post operative urine samples and stones was performed to clarify the relationship between urinary tract infections and stone formation. Commonest pathogens recovered by bacteriological analysis were identified as E.coli (38.1%) followed by Pseudomonas aeruginosa (33.3%), Proteus mirabilis (12%), klebsiella pneumonia (10%), Enterococci (4.5%) and coagulase negative Staphylococcus (2.4%) and were further confirmed by16S rDNA sequencing and phylogenetic analysis. The isolated organisms were tested for antibiotic sensitivity and the resistant strains were additionally screened for biofilm formation. We hypothesize that, recurrent renal calculi formation may be attributed to antibiotic resistant biofilm forming urinary tract infections along with environmental habitats.